AB1158 Quality of Life in Patients with Active Peripheral SPA is Similarly Impaired as in Other Rheumatic Diseases and Influenced by Disease Activity But not Disease Duration. (9th June 2015) - Mease, P.; van der Heijde, D.; Mittal, M.; Joshi, A.; Xu, Y.; Pangan, A.; Song, I.-H.
Abstract : Background: There is a lack of data on the quality of life (QoL) in patients (pts) with active peripheral spondyloarthritis (pSpA). Objectives: The objective was to assess the QoL in pts with pSpA, and compare it to the QoL across other rheumatic diseases. Methods: Data for this analysis originated from the following five trials of adalimumab versus placebo for various rheumatic diseases: ABILITY-2 for pSpA; ABILITY-1 for non-radiographic axial SpA (nr-axSpA); ATLAS for ankylosing spondylitis (AS); DE019 for rheumatoid arthritis (RA), and ADEPT for psoriatic arthritis (PsA). In each dataset, the QoL at baseline was measured by the Short Form 36 (SF-36) mental component summary (MCS) and physical component summary (PCS). Differences from the norms for an age-and gender- matched healthy control population at baseline were calculated for each rheumatic disease. In order to assess the influence of disease activity and disease duration on MCS and PCS, patients were stratified into tertiles by disease activity or disease duration. The difference in MCS and PCS and the 95% CI for the extreme tertiles (lower vs higher) was compared to that for an age- and gender-matched normal population. Lower vs. higher disease activity was defined as: Bath Ankylosing Spondylitis Disease Activity Score (BASDAI) ≤4.8 or >6.5 for pSpA; ≤6.0 and >7.1 for nr-axSpA; ≤5.6 and >7.1 for AS; 28-joint count disease activity score based on C-reactive protein [DAS28(CRP)] ≤5.3 and >6.1, for RA; Patient's global assessment (PtGA) ≤39 and >60 for PsA. Shorter vs. longer disease duration was defined as: ≤2.6 or >3.4 years (yrs) for pSpA; ≤0.5 or >2.3 yrs for nr-axSpA; ≤5.2 or >13.4 yrs for AS; ≤5 or >12.9 yrs for RA; ≤4.2 or >11.2 yrs for PsA. Results: Across the five rheumatic diseases, the differences in SF-36 MCS and PCS compared to the norms for an age- and gender-matched population were similar (table ). However, the observed difference from the norm was greater for the PCS than for the MCS indicating a greater impact on physical function. For each disease, higher disease activity, but not longer disease duration was associated with a significantly greater difference in PCS and MCS compared to the norms. Conclusions: Patients with pSpA suffer from a poor quality of life, to a similar extent compared with the other rheumatic diseases included here. Results indicate that current disease activity and not disease duration contributes to this impairment of physical and mental health. Acknowledgements: AbbVie sponsored the studies, contributed to their design, participated in the collection, analysis, and interpretation of the data, and in the writing, reviewing, and approval of the final version. Statistical support was provided by Shufang Liu, PhD; medical writing support was provided by Naina Barretto, PhD, of AbbVie Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Consultant for: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, D. van der Heijde Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Chugai, Daiichi, Eli Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, and Vertex, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Chugai, Daiichi, Eli Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, and Vertex, M. Mittal Employee of: AbbVie, A. Joshi Employee of: AbbVie, Y. Xu Employee of: AbbVie, A. Pangan Employee of: AbbVie, I.-H. Song Employee of: AbbVie